Teacher's Strategy in Improving Student Learning Discipline in PAI Subject for Class XI IPS 4 at SMAN Lemahabang - Berlian Hanum Salasabilah; Amirudin; Iqbal Amar Muzaki (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to analyze teachers' strategies for improving students' learning discipline in PAI subjects for Class XI Ips 4 at SMAN 1 Lemahabang. The thing that becomes an obstacle in the learning process in class and outside the classroom is the problem of discipline. Because discipline can hinder the learning process and can reduce the effectiveness of PAI learning. Therefore, it is important to determine learning strategies in overcoming these problems by using varied learning methods that can improve students' learning discipline to be more effective and conducive. This research uses a qualitative approach with a case study method. Data was collected through classroom observations, interviews with teachers and students, as well as analysis of related documents. The results of this research show that teacher Pai's strategy in improving the learning discipline of class XI Ips 4 students at SMAN 1 Lemahabang using varied methods can motivate students' learning in PAI learning. So that it can make students more active and involved in the learning process. Therefore, the use of this varied method is an effective learning method in solving problems in the classroom that are less conducive and also students who are less disciplined in the learning process in the classroom.